ChemInform Abstract: C—H Arylation of Azaheterocycles: A Direct Ligand‐Free and Cu‐Catalyzed Approach Using Diaryliodonium Salts. Issue 3 (January 2015) - Kumar, Dalip; Pilania, Meenakshi; Arun, V.; Pooniya, Savita
Abstract This efficient direct C‐H arylation strategy gives access to various arylated azaheterocycles by using readily available diaryliodonium salts.